Синтез різнотемпових дискретних систем керування із врахуванням рідких вимірювань вихідних координат багатовимірного об’єкта - Romanenko, V. D.; Krasnichuk, V. N. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A procedure for multirate discretization of a continuous mathematic plant model in state space under high discretization frequency of state vectors and control and low discretization frequency of the output measurement vector is considered. The procedure allows considering occasional measurements of the variable plant output coordinates when forming the control vector. A method for design of a multirate digital controller is also given.